Corals and stromatoporoids from the Ordovician and Silurian of Kronprins Christian Land, Northeast Greenland - Scrutton, Colin T. (Meddelelser om Grønland, 1975)
Corals and stromatoporoids are described from the Centrum Formation, Drømmebjerg Formation and the boulder conglomerate at the base of the Profilfjeldet Formation in the Lower Palaeozoic sequence at the southern end of Kronprins Christian Land, northeast Greenland. The coral faunas strongly suggest an Upper Ordovician (Cincinnatian) age for the upper half of the Centrum Formation. The Drømmebjerg Formation has brachiopods in common with the Offley Island Formation of northwest Greenland and is therefore considered to be, at least in part, of Upper Llandovery age. Lower and Middle Llandovery sediments may be missing. Corals from the boulder conglomerate at the base of the Profilfjeldet Formation suggest that limestone deposition may have persisted into the early Wenlock. In the systematic section, two new tabulate coral species are named - Saffordophyllum troedssoni and Paleofavosites cowiei. The collections contain representatives of two genera of stromatoporoids, eight genera of rugose corals, eight genera of tabulate corals and two genera of heliolitids. Specific North American and Eurasian elements can be recognised in the faunas.